P42 | PANCREATIC CANCER STEM CELLS AND FUNCTIONAL CHARACTERIZATION OF MIR-216A-5P (European Journal of Histochemistry)
Pancreatic ductal adenocarcinoma (PDAC) is the third leading cause of cancer-related death. Its poor prognosis is closely related to late-stage diagnosis, which results from both nonspecific symptoms and the absence of biomarkers for early diagnosis1. MicroRNAs (miRNAs) exert a regulatory role in numerous biological processes, and their aberrant expression has been found in a broad spectrum of diseases, including cancer2. Cancer stem cells (CSCs) represent a driving force for PDAC initiation, progression, and metastatic spread. Our previous research highlighted the interesting behavior of miR-216a-5p and miR-125a-5p related to PDAC progression and the CSC phenotype. Our study aimed to evaluate the effect of miR-216a-5p on the acquisition or suppression of pancreatic CSC traits. BxPC-3, AsPC-1 cell lines, and their CSC-like models were transfected with miR-216a-5p mimics and inhibitors. We evaluated their impact on the expression of CSC surface markers (CD44/CD24/CxCR4), ALDH1 activity, pluripotency- and EMT-related gene expression, and clonogenic potential. Our results show that miR-216a-5p enhances the expression of CD44/CD24/CxCR4 while negatively affecting the activity of ALDH1 and the expression of EMT genes. Comprehensively, our results provide further knowledge on the role of miRNAs in pancreatic CSCs. Moreover, they corroborate our previous findings about miR-216a-5p’s potential dual role and miR-125a-5p’s promotive function in PDAC.